2023
DOI: 10.1039/d3sc01240a
|View full text |Cite
|
Sign up to set email alerts
|

A highly enantioselective intramolecular 1,3-dipolar cycloaddition yields novel pseudo-natural product inhibitors of the Hedgehog signalling pathway

Abstract: De novo combination of natural product (NP) fragments by means of efficient, complexity- and stereogenic character-generating transformations to yield pseudo-natural products (PNPs) may explore novel biologically relevant chemical space. Pyrrolidine-...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…In this regard, it often draws inspiration from the biological relevance and chemical diversity of natural products . The need to explore new chemical space has been facilitated by strategies such as fragment-based compound design. For example, formal fragmentation of natural products and subsequent recombination, in various arrangements, can deliver novel analogues. Such analogues, per se inaccessible through biosynthetic pathways, may inherit the biological and chemical properties of the original natural products and, thus, are called pseudo-natural products, a principle introduced by Waldmann et al that has been shown effective for identifying new biologically active compounds. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it often draws inspiration from the biological relevance and chemical diversity of natural products . The need to explore new chemical space has been facilitated by strategies such as fragment-based compound design. For example, formal fragmentation of natural products and subsequent recombination, in various arrangements, can deliver novel analogues. Such analogues, per se inaccessible through biosynthetic pathways, may inherit the biological and chemical properties of the original natural products and, thus, are called pseudo-natural products, a principle introduced by Waldmann et al that has been shown effective for identifying new biologically active compounds. …”
mentioning
confidence: 99%
“… 5 7 Such analogues, per se inaccessible through biosynthetic pathways, may inherit the biological and chemical properties of the original natural products and, thus, are called pseudo-natural products, a principle introduced by Waldmann et al that has been shown effective for identifying new biologically active compounds. 8 11 …”
mentioning
confidence: 99%